(3GdYedjGJ GdeUQajI GdNGQLjIs - (3GdQGhj(B, (3NGdO hgjHs ((3YeGfs (3OGQ GdefGgLs, 2000)
(3WHjYI GdYedjGJ GdeUQajI GdOhdjI(B- (3GdHWGbGJ GdHdGSJjcjI hGdHWGbI GdPcjI(B- (3GdJShjb GdeUQaj hJLRFI GdShb(B- (3GdJMOj GdOhdj ddeUGQa(B- (3UfOhb GdfbO GdOhdj hGdHfc GdOhdj(B- (3GdSMhHGJ GdeSJfOjI(B- (3GdNjGQGJ(B.s
Keywords: (3GdYedjGJ GdeUQajIs; (3GdeUGQa GdNGQLjIs